Best Level of Parameters for a Critical Buckling Load for Circular Thin- Walled Structure Subjected to Bending - Al-Khafaji, Hussein M. H. (Al-Khwarizmi Engineering Journal, 2019)
Circular thin walled structures have wide range of applications. This type of structure is generally exposed to different types of loads, but one of the most important types is a buckling. In this work, the phenomena of buckling was studied by using finite element analysis. The circular thin walled structure in this study is constructed from; cylindrical thin shell strengthen by longitudinal stringers, subjected to pure bending in one plane. In addition, Taguchi method was used to identify the optimum combination set of parameters for enhancement of the critical buckling load value, as well as to investigate the most effective parameter. The parameters that have been analyzed were; cylinder shell thickness, shape of stiffeners section and the number of stiffeners. Furthermore, to verify the contribution of parameters on buckling response, the analysis of variance technique (ANOVA) method was implemented, which gave the contribution weight as percentages. The analysis of results by these two methods showed that the more effective parameter on the critical buckling load was the thickness of cylinder’s shell and the lowest effective was the number of stiffeners The values of parameters that gave the best critical buckling load combination were: 1) the ratio of cylinder’s diameter to thickness of its shell was 133, 2) the ratio of the depth to thickness of stiffeners was1.6, and 3) the number of stiffeners was 12.